2013
DOI: 10.1007/s00436-013-3549-2
|View full text |Cite
|
Sign up to set email alerts
|

Naegleria fowleri glycoconjugates with residues of α-d-mannose are involved in adherence of trophozoites to mouse nasal mucosa

Abstract: We analyzed the possible role of glycoconjugates containing α-D-mannose and α-D-glucose residues in adherence of trophozoites to mouse nasal epithelium. Trophozoites incubated with 20 μg of one of three different lectins which preferentially recognized these residues were inoculated intranasally in Balb/c mice. Mouse survival was 40% with Pisum sativum and Canavalia ensiformis and 20% with Galanthus nivalis amebic pretreatment, compared with 0% survival for control animals administered trophozoites without pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Another in vitro study demonstrated the differential carbohydrate expression of N. fowleri and N. gruberi (CervantesSandoval et al, 2010). These findings were supported by those of Carrasco-Yepez et al (2013), who reported that mannose residues are essential for N. fowleri to adhere to mouse nasal mucosa.…”
Section: Mechanisms Of Pathogenicitysupporting
confidence: 81%
“…Another in vitro study demonstrated the differential carbohydrate expression of N. fowleri and N. gruberi (CervantesSandoval et al, 2010). These findings were supported by those of Carrasco-Yepez et al (2013), who reported that mannose residues are essential for N. fowleri to adhere to mouse nasal mucosa.…”
Section: Mechanisms Of Pathogenicitysupporting
confidence: 81%
“…However, a 70‐kDa immunoreactivity protein species was found at a higher level for N fowleri ; suggesting that such differences exhibited a higher level of attachment to ECM components in N fowleri than N lovaniensis. 2 Other studies have demonstrated the differential carbohydrate expression of N fowleri and N gruberi suggesting that these differences are essential for N fowleri to adhere to mouse nasal mucosa 26,27 As we can observe, some of these pathogenicity factors are not exclusive to N fowleri , since they are also present in nonpathogenic Naegleria species with different level of expression 1,2,13,26,27 . While other virulence factors have only been studied in N fowleri and not in nonpathogenic Naegleria species .…”
Section: Introductionmentioning
confidence: 73%
“…About carbohydrates, there are reports that have shown that these participate in a very important way during the protozoan invasion process 69‐71 . In vitro experiments have shown that the trophozoites of N fowleri have high levels of glycoconjugates on their surfaces, mainly α‐ d ‐glucose, α‐ d ‐mannose, N ‐acetylneuraminic acid and terminal α‐L‐fucose residues, 26,72,73 and in vivo experiments have demonstrated the possibility that some of the glycoproteins found in N fowleri represent a factor of adherence to host cells 27 . As these glycoproteins identified in N fowleri could represent key adhesion factors to the nasal epithelium and probably would be important factors in the progression of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations